Existence Result for a Class of Elliptic Systems with Indefinite Weights in R2. (12th March 2008) - Zhang, Guoqing; Liu, Sanyang
Abstract : We obtain the existence of a nontrivial solution for a class of subcritical elliptic systems with indefinite weights inR 2 . The proofs base on Trudinger-Moser inequality and a generalized linking theorem introduced by Kryszewski and Szulkin.